Evaluation of prevalence of different types of cancer and its chemotherapy in various ethnic groups of Pakistan: A retrospective study - Danish Ali; Syed Baqir Shyum Naqvi; Muhammad Iqbal Nasiri; Kamran Ahmed; Kamran Zaheer; Muhammad Azeem; Muhammad Masoom Akhtar (Brazilian Journal of Pharmaceutical Sciences, 2020)
The objective of the study was to evaluate different types of cancer and its chemotherapy in various ethnic groups of Pakistan. Ethnic groups includes, Pukhtoons, Punjabis, Sindhis, Muhajirs, Siraikis, Memoons, Hazaras, Hindkos, Baltis, Gilgitis, Kashmiris, and Afghanis. The data was collected from well reputed hospitals located in the different provinces of Pakistan. The collected data was taken from 15 hospitals where around 8500 patients visited during 2010 to 2017. From the visited patients, 8356 were analyzed for their ethnicity, age and sex while, 144 patients (male 77 and female 67) were excluded from analysis due to incomplete information or loss of follow-up. Among 8356 patients, 3762 were male (45%) whereas, 4594 were female (55%). The chemotherapy was carried out as per National Comprehensive Cancer Network guidelines (NCCN- guidelines). The most common five prevalent cancer among these ethnic groups were Head and Neck, Blood, Respiratory, Genito-urinary and Breast cancer. The most common cancer in female was breast cancer while, head and neck cancer was more prevalent in male. It can be concluded that the prevalence of cancer in Pakistan is very alarming, which may be due to lack of awareness, illiteracy, lack of national cancer control programs, and economics issues.